Конечноэлементный анализ деформативности и прочности полимерных элементов конструкций с учетом вязкоупругости материала - Шилько, С. В.; Старжинский, В. Е.; Петроковец, Е. М.; Гавриленко, С. Л. (My University, 2014)
Разработана методика анализа деформативности и прочности элементов конструкций сложной формы с учетом вязкоупругости материала. Для получения реологических констант выполнена идентификация вязкоупругой модели Прони по результатам механических испытаний стандартных образцов на релаксацию при сжатии. Рассмотрены примеры расчета зубчатого колеса и сильфона из полиамида.

Technique for analysis of deformation and strength of construction elements of complex shape has been developed by taking into account material viscoelasticity. Examples of calculation for gear and bellows made of polyamide have been considered. Identification of the viscoelastic Prony model has been carry out by results of mechanical compression tests on relaxation of standard samples in order to derive rheological constants.
Finite element analysis of deformation and strength of construction polymeric elements by taking into account material viscoelasticity
Keywords: полимерные композиты; прочность; модель Прони; метод конечных элементов; зубчатое колесо; сильфон; polymeric composites; deformation; strength; viscoelasticity; Prony model; finite element method; gear; bellows